PENGARUH KESADARAN SITUASI IBU HAMIL DENGAN FREKUENSI KUNJUNGAN ANTENATAL DI WILAYAH KERJA PUSKESMAS WARU KABUPATEN PAMEKASAN TAHUN 2016 - Sendy Ayu Mitra Uktutias; Niniek Lely Pratiwi; Windhu Purnomo (Buletin Penelitian Sistem Kesehatan, 2018)
Basic Health Research Results (Riskesdas) conducted by the Ministry of Health shows that the coverage of K4 during the last 3 years in 2010–2013 is the year 2010 by 86.85% and the year 2013 of 87.48%. The lack of utilization of ANC by pregnant women is associated with many factors, one of which is the lack of awareness of pregnant women about the importance of pregnancy care. The purpose of this study analyzed the influence of awareness of the situation of pregnant women with the frequency of antenatal visits. The research method was analytic observational with cross sectional study design. The study sample was 38 pregnant women who lived in the working are at waru public health center’s. The sampling technique using simple random sampling. Data collection using primary data by questionnaire and secondary data with the instrument KIA book. Data were processed and analyzed by using frequency distribution and inferential analyze of linier regression with a significance level of 5% (p = 0.05). The results of linear regression analysis in pregnant women showed significant value of β 0.684 (β > 0.500), that the awareness of the situation had an effect on the frequency of antenatal care. A good situation awareness is a necessary process to influence the decision to act, it is a pregnancy test and can be seen the frequency of antenatal care of a pregnant woman. This conclusion Waru public health center’s is a health clinic located in the highlands. Still less maximal antenatal care visits because of the support and access to antenatal care. It is suggested to raise awareness of pregnant women situation through family involvement, husband as reinforcement factor in support of improvement of antenatal care examination.